2006
DOI: 10.1016/s0840-4704(10)60240-2
|View full text |Cite
|
Sign up to set email alerts
|

Models of Primary Care Service Delivery in Ontario: Why Such Diversity?

Abstract: A surprisingly large and ever-growing number of alternative models of primary care service delivery have been developed in Ontario. The models are relatively poorly understood, and it is unclear why there are so many of them. What needs of providers and of government as payer are they attempting to address? Through a literature review and interviews with key informants, we sought to explain why there are so many models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…1 FHTs evolved from several earlier Ontario pilots, among which are Community Health Centers (CHCs), Family Health Networks (FHNs), and Family Health Groups (FHGs). 10 CHCs, originating in 1980, are more likely to serve rural, low-income, or minority populations. Physicians are reimbursed by salary, and practices are likely to have multidisciplinary teams.…”
Section: Implementation Of the Fht Model In Ontariomentioning
confidence: 99%
“…1 FHTs evolved from several earlier Ontario pilots, among which are Community Health Centers (CHCs), Family Health Networks (FHNs), and Family Health Groups (FHGs). 10 CHCs, originating in 1980, are more likely to serve rural, low-income, or minority populations. Physicians are reimbursed by salary, and practices are likely to have multidisciplinary teams.…”
Section: Implementation Of the Fht Model In Ontariomentioning
confidence: 99%
“…The study was designed to describe and compare the structure and process of care within 4 primary health care delivery models in Ontario, Canada: fee for service (FFS), family health networks (FHNs), health service organizations (HSOs), and community health centers (CHCs). 11 From 2004 through 2006 practices operating within these 4 models were responsible for delivering primary care to most of the Ontario population. Table 1 displays these models, as well as the family health groups (FHGs) to which most practices in the FFS group eventually transitioned, and their essential characteristics.…”
Section: Delivering Chronic Dise a Se Managementmentioning
confidence: 99%
“…9 There are, however, important variations in the delivery of chronic disease management programs and services in primary care. 10,11 Recent studies suggest that the way chronic disease management is delivered in general practice is highly infl uenced by organizational factors. 12,13 Various studies have suggested that highquality chronic disease management can be promoted by fi nancial incentives, capitated payment structures, improved Internet technology infrastructure, and the wider use of nonmedical health care professionals.…”
mentioning
confidence: 99%
“…The models vary by funding structure, but also by organizational structure and stated priorities. 11 We conducted this study to compare the delivery of preventive services by practices in the four funding models and to identify organizational factors associated with superior preventive care. This study is part of a larger evaluation of primary care models in Ontario funded by the Ontario Ministry of Health and Long-Term Care through its Primary Health Care Transition Fund.…”
mentioning
confidence: 99%